The microbiota-gut- hippocampus axis - Salami, Mahmoud; Soheili, Masoud (Frontiers in Neuroscience, 2022)
It is well known that the intestinal bacteria substantially affect physiological processes in many body organs. Especially, through a bidirectional communication called as gut-microbiota-brain axis, the gut microbiota deeply influences development and function of the nervous system. Hippocampus, as a part of medial temporal lobe, is known to be involved in cognition, emotion and anxiety. Growing evidence indicates that the hippocampus is a target of the gut microbiota. We used a broad search linking the hippocampus with the gut microbiota and probiotics. All experimental studies and clinical trials published until end of 2021 were reviewed. Influence of the gut microbiota on the behavioral, electrophysiological, biochemical and histological aspects of the hippocampus were evaluated in this review. The effect of disrupted gut microbiota and probiotic supplements on the microbiota-hippocampus link is also considered. Studies show that a healthy gut microbiota is necessary for normal hippocampus dependent learning and memory and synaptic plasticity. The known current mechanisms are production and modulation of neurotrophins, neurotransmitters and receptors, regulation of intracellular molecular processes, normalizing the inflammatory/anti-inflammatory and oxidative/antioxidant factors, and histological stability of the hippocampus. Activity of the hippocampal neuronal circuits as well as behavioral functions of the hippocampus positively respond to different mixtures of probiotic bacteria. Growing evidence from animal researches indicate a close association between the hippocampus with the gut microbiota and probiotic bacteria as well. However, human studies and clinical trials verifying such a link are scant. Since the most of papers on this topic have been published over the past 3 years, intensive future research awaits.